Electronic Signatures in Saudi Arabia's Contemporary Digital Era: Examining Authenticity and Attribution Through the Lens of Islamic Law - Hajed A. Alotaibi; Bandar A. Alyahya; Salem R. Alazizi (MILRev: Metro Islamic Law Review, 2026)
The rapid digitalization of Saudi Arabia under Vision 2030 raises a fundamental jurisprudential question: whether Islamic evidentiary doctrines grounded in moral intentionality can be authentically replicated within algorithmic authentication systems. This study is guided by three research questions: (1) how Saudi digital trust laws reconcile technological authenticity with Islamic evidentiary doctrines that require moral responsibility; (2) whether electronic signatures can satisfy the classical Sharīʿah requirements of intention (niyyah) and attestation (tawthīq), traditionally fulfilled through human witnesses; and (3) what interpretive logic enables statutory law and Islamic jurisprudence to generate both technical reliability and spiritual legitimacy. Employing a doctrinal-comparative qualitative methodology, the study integrates maqāṣid al-Sharīʿah analysis, analogical legal reasoning, and functional equivalence assessment. The analysis draws on the Digital Trust Services Regulation (2025), the Law of Evidence (2022), and the Civil Transactions Law (2024), alongside classical fiqh sources and comparative frameworks from the EU eIDAS Regulation, Malaysia, and the Dubai International Financial Centre (DIFC). The findings reveal that cryptographic authentication functions as the contemporary equivalent of classical tawthīq and bayyinah in establishing legal certainty and evidentiary reliability. Furthermore, Islamic ethical principles such as Amānah (trustworthiness) and ṣidq (truthfulness) are institutionalized as enforceable compliance obligations rather than merely aspirational moral values. The study also demonstrates that Saudi Arabia's digital trust architecture reproduces classical models of delegated moral custodianship through state-regulated certification and oversight mechanisms. This research contributes to the literature by extending maqāṣid-based modernization theory into the domain of digital governance, offering the first systematic comparative analysis of Saudi Arabia's hybrid normative framework, and proposing the concept of Digital Maqāṣid Governance as a transferable model for Muslim-majority jurisdictions seeking to integrate Sharīʿah ethics with contemporary digital infrastructure.